Stimulation of gonad maturation in mullet fish Mugil dussumieri using MT, E2, hCG, and Ovaprim hormone - Cahyono, Tatak Dwi; Junior, Muhammad Zairin; Carman, Odang (Jurnal Akuakultur Indonesia, 2019)
ABSTRACT The present study is a preliminary research for producing mullet fry to aquaculture. The research aimed to evaluate stimulation of gonad maturation in mullet (Mugil dussumieri) using hormones. The method used for research was completely randomized design consisting of three treatments and each individual replication was repeated three times. Two experiments were conducted separately with different treatments. First experiment used 9-14.7 cm body length of fish treated with different hormone injections i.e. 4 mg/kg 17α-methyltestosterone (MT), 0.07 mg/kg estradiol-17β (E2), and 0.5 ml/kg 0.9% physiological solution as control. Second experiment used 10-31 cm body length fish treated with 750 IU/kg chorionic gonadotropin (hCG), 0.5 ml/kg Ovaprim, and 0.9% physiological solution as control. Gonadosomatic index (GSI) value of the first experiment on day 60 showed that GSI of E2 treatment (1.31±0.94%) was higher than both MT treatment (1.00±0.51%) and control (0.54±0.20%). On the other hand, the second experiment on day 60 showed that GSI of hCG treatment (7.18±0.59%) was higher than both Ovaprim treatment (3.29±2.66%) and control (6.72±0.32%). Egg diameter frequency distribution for control in the first experiment on day 30 showed that egg size ranged from 9−144 µm. Egg diameter for E2 and MT treatments on day 60 showed that egg size ranged from 9−243 µm and were higher than control. In the second experiment, egg diameter on day 30 for control showed that egg size ranged from 9-144 µm, hCG treatment showed egg size ranged from 9−441 µm, while Ovaprim egg size ranged from 9-111 µm. Blood glucose, blood cholesterol, testosterone and estradiol hormone level in the first and second experiment showed no significant difference. The results showed that estradiol-17β and 17α-methyltestosterone induction in 9-14.7 cm body length mullet increase gonad maturity to stage II while hCG induction in 10-31 cm body length mullet increase gonad maturity to stage III. Keywords : estradiol-17β, hCG, 17α-methyltestosterone, Mugil dussumieri, Ovaprim ABSTRAK Penelitian merupakan rintisan untuk menghasilkan benih ikan belanak dalam wadah budidaya. Penelitian ini bertujuan untuk mengevaluasi pematangan gonad ikan belanak Mugil dussumieri menggunakan hormon. Penelitian dilakukan menggunakan rancangan acak lengkap yang terdiri dari tiga perlakuan dan tiga kali ulangan individu. Terdapat dua percobaan dengan perlakuan berbeda dan dilakukan secara terpisah. Percobaan pertama menggunakan ikan berukuran 9−14.7 cm dengan hormon 17α-metiltestosteron (MT) 4 mg/kg, estradiol-17β (E2) 0.07 mg/kg dan kontrol larutan fisiologis 0.9% 0.5 ml/kg. Percobaan kedua menggunakan ikan berukuran 10−31 cm dengan human chorionic gonadotropin (hCG) 750 IU/kg, Ovaprim 0.5 ml/kg dan kontrol larutan fisiologis 0.9 % 0.5 ml/kg. Nilai gonadosomatic index (GSI) percobaan pertama pada hari ke-60 menunjukkan bahwa pemberian estradiol-17β (1.31±0.94%) lebih tinggi dibandingkan 17α-metiltestosteron (1.00±0.51%) dan kontrol (0.54±0.20%). Hasil percobaan kedua pada hari ke-60 nilai GSI menunjukkan bahwa pemberian hCG (7.18±0.59%) lebih tinggi dibandingkan Ovaprim (3.29±2.66%) dan kontrol (6.72±0.32%). Sebaran frekuensi diameter telur pada percobaan pertama untuk kontrol hari ke-30 menunjukkan kisaran 9−144 µm. Sebaran frekuensi diameter telur untuk estradiol-17β dan 17α-metiltestosteron hari ke-60 menunjukkan kisaran 9−243 µm lebih banyak dibandingkan kontrol. Sebaran frekuensi diameter telur pada percobaan kedua untuk kontrol hari ke-30 menunjukkan kisaran 9−144 µm, hCG 9−441 µm sedangkan Ovaprim hanya 9−111 µm. Kadar glukosa darah, kolesterol darah, hormon testosteron dan estradiol pada percobaan pertama dan percobaan kedua menunjukkan tidak terdapat perbedaan yang nyata. Hasil penelitian menunjukkan bahwa induksi hormon estradiol-17β dan 17α-metiltestosteron pada ikan berukuran 9−14.7 cm dapat meningkatkan kematangan gonad mencapai TKG II sedangkan induksi hormon hCG pada ikan berukuran 10−31 cm dapat meningkatkan kematangan gonad mencapai TKG III. Kata kunci : estradiol-17β, hCG, 17α-metiltestosteron, Mugil dussumieri, Ovaprim